Hadist-hadist tentang Musik Studi Komparatif Pemahaman Ibnu Hazm dan Al-Mubarakfuri - Naamuddin, Naamuddin; Matondang, Husnel Anwar; Is, Fadhilah (Lembaga Yasin AlSys, 2024)
This research aims to examine the types of music (comparative study of the understanding of Ibn Hazm and Al-Mubaraktfur. This research uses qualitative descriptions or literature. The results of the research show that Ibn Ḥazm believes that the law of everything for which there is no clear argument about it is permissible, This includes music as is the general verse of Qs. al-Baqarah: 29. There are many shortcomings in the hadiths which forbid music, including the weakness of the narrator, as well as the use of words in the narration which raises doubts in it. al-Mubārakfūrī, music is something that is forbidden, including playing various types of musical instruments such as tambourines, flutes, guitars, etc. Differences between scholars on this issue, especially in the views of Ibn Ḥazm and al-Mubārakfūrī, do not include differences of opinion that are permissible for someone choose an opinion that he believes in based on the arguments he has heard from both of them. This is because there is a clear argument that invalidates one of the two views. In this case, Ibn Ḥazm's opinion regarding ḥadīṡ which he thought was weak turned out to be ḥadīṡ which is ṣaḥīḥ and is agreed upon by most scholars. Meanwhile, al-Mubārakfūrī said that music and musical instruments were haram, which was absolute, because on the other hand he permitted this.